Analysis of the BAS OH band reveals a non-statistical incorporation of Al into the MOR framework - Rubes, Miroslav; Koudelková, Eva; Vaculík, Jan; Trachta, Michal; Bulánek, Roman; Bludsky, Ota (Elsevier Science BV, 2021)
H-MOR zeolites with different Si/Al ratios were investigated by the combined use of FT-IR spectroscopy, calorimetry, and periodic DFT calculations. Our analysis of 14 different Br?nsted acid sites (BAS) was carried out with the ?/r correlation method parameterized to reproduce the OH band shape for the high silica H-MOR(32) sample. The estimated populations clearly show that the Al distribution exhibits non-statistical behavior. The preferential incorporation of Al into the T3 and T4 framework positions is in excellent agreement with the X-ray study of Alberti et al. on natural mordenites. This suggests that the Al distribution is very similar in both high silica and aluminum rich MOR materials. The analysis of H-MOR with lower Si/Al ratios is complicated by the interaction of the adjacent BAS. This effect leads to significant changes in relative energies that determine populations of the individual sites. Our interpretation of the experimental data is further supported by a very good agreement between calculated CO adsorption enthalpies and calorimetric measurements. An anomalously large dispersion stabilization is found for adsorption complexes located in the side pocket of the MOR framework.
Analýza BAS OH skupin vykazujících nestatistickou inkorporaci Al do MOR struktury
Keywords: acidic zeolites; ab initio calculations; IR spectra; isosteric heats; CO adsorption; kyselé zeolity; ab initio výpočty; IR spektra; isosterické teplo; CO adsorpce